A Novel Current-Mode OTA-C Universal Filter - Abuelma’atti, M.T. (2007)
A novel current-mode biquad circuit is presented. The circuit uses two single-output-, one multiple-output-operational transconductance amplifiers (OTAs), two grounded capacitors and can realize lowpass, highpass, bandpass, notch, lowpass notch, highpass notch and allpass responses from the same topology. The parameters ωo and ωo/Qo enjoy independent electronic tunability. Simulation results are included.